(untitled) (Journal of the College of Basic Education, 2022)
The research contained four chapters. The first included the research problem, which the researcher felt necessary to delve into this study, in which he dealt with ((aesthetic values ​​in school songs)).Then the importance of the research and the aim of the research, which included: revealing the aesthetic values ​​in the school songs. As for the limits of the research, it was limited to the aesthetic values ​​in the school songs composed and composed in the school curricula for the primary stage of the book (Reading) for the period from (2003-2016) in the schools of the Republic of Iraq, as well as the definition of the research terms. The second chapter included the theoretical framework and previous studies. It consists of three topics:The first topic / beauty in music and chanting. The second topic / school songs. The third topic / elements of the school anthem. This was followed by the indications that resulted from the theoretical framework.